Full‐depth englacial vertical ice sheet velocities measured using phase‐sensitive radar. Issue 12 (11th December 2014) - Kingslake, Jonathan; Hindmarsh, Richard C. A.; Aðalgeirsdóttir, Guðfinna; Conway, Howard; Corr, Hugh F. J.; Gillet‐Chaulet, Fabien; Martín, Carlos; King, Edward C.; Mulvaney, Robert; Pritchard, Hamish D.
Abstract We describe a geophysical technique to measure englacial vertical velocities through to the beds of ice sheets without the need for borehole drilling. Using a ground‐based phase‐sensitive radio echo sounder (pRES) during seven Antarctic field seasons, we measure the temporal changes in the position of englacial reflectors within ice divides up to 900 m thick on Berkner Island, Roosevelt Island, Fletcher Promontory, and Adelaide Island. Recorded changes in reflector positions yield "full‐depth" profiles of vertical ice velocity that we use to examine spatial variations in ice flow near the divides. We interpret these variations by comparing them to the results of a full‐Stokes simulation of ice divide flow, qualitatively validating the model and demonstrating that we are directly detecting an ice‐dynamical phenomenon called the Raymond Effect. Using pRES, englacial vertical ice velocities can be measured in higher spatial resolution than is possible using instruments installed within the ice. We discuss how these measurements could be used with inverse methods to measure ice rheology and to improve ice core dating by incorporating pRES‐measured vertical velocities into age modeling.